The Effect of Agricultural Modernisation on Food Security and Economic Growth - Demurian, Syadit; Syananda (Yayasan Cinta Negara Indonesia, 2025)
This study aims to analyze the effect of agricultural modernization on food security and economic growth in Indonesia. Agricultural modernization, which includes the application of new technologies, improved irrigation systems, and more efficient use of fertilizers and pesticides, is believed to increase agricultural output and strengthen food security. However, its impact on the regional and national economy is still a topic that requires in-depth study. This study uses quantitative methods with regression analysis to measure the relationship between agricultural modernization and food security and economic growth variables. The data used includes statistics on agricultural production, food consumption levels, and regional economic indicators over the past 10-year period. The results show that agricultural modernization has a significant positive impact on food security, especially in increasing food productivity and reducing dependence on imports. In addition, it has also contributed to economic growth, by increasing farmers' income and creating jobs in the agricultural sector. However, the study also found challenges in the uneven application of technology across regions, which could widen economic disparities between regions. Therefore, policies that support technology extension and equitable access to agricultural modernization are needed to maximize its benefits